Capital humano y generación de valor en la empresa - Merzthal, Jorge (2017)
It seems undoubted that human capital is currently the key idea of companies. But the evolution of knowledge, technology, training and collaboration between companies constitute a generation of value within the company and with great potential for consumers / clients. This generation of value extends to competitiveness in companies and diverse cultural contexts. Training is a key element in the entire structure of organizations and the connection with other companies sharing training will form networks which generate value for other companies as a whole to compete better and achieve higher levels of productivity in local and international markets, linking human capital and generation of value between companies through training. The interaction between human capital and training is addressed by means of training through learning and as a result as a benchmark of productivity and competitiveness. The generation of value through the client, economic value, and especially, value from strategic alliances and training, are all highlighted.